2013
DOI: 10.1002/app.39003
|View full text |Cite
|
Sign up to set email alerts
|

Microwave curing of epoxy polymers reinforced with carbon nanotubes

Abstract: The driver for this study is the observation that heating of carbon nanotubes (CNTs) with electromagnetic field can offer a more efficient and cost-effective alternative in heat transfer for the production of composites. The idea of this study is twofold; CNT can work as microwave (MW) radiation susceptors and they can act as nanoreinforcements in the final system. To test these assumptions, a household oven was modified to control the curing schedule. Polymers with different CNT concentrations were prepared (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Originally, microwaves are used for communication/ telecommunication purposes but recently they have gained very fast popularity for processing of polymers based materials and advanced materials such as polymer matrix composites (PMC) [3]. Many research groups have investigated the accelerated curing of nanocomposites in order to gain high strength [4][5][6][7]. However, the success has been very limited due to lack of understanding the behavior of dielectric permittivity of polymer nanocomposites because most of the polymers exhibit very low dielectric losses in the GHz region and it is difficult to heat them by microwaves [8].…”
Section: Introductionmentioning
confidence: 99%
“…Originally, microwaves are used for communication/ telecommunication purposes but recently they have gained very fast popularity for processing of polymers based materials and advanced materials such as polymer matrix composites (PMC) [3]. Many research groups have investigated the accelerated curing of nanocomposites in order to gain high strength [4][5][6][7]. However, the success has been very limited due to lack of understanding the behavior of dielectric permittivity of polymer nanocomposites because most of the polymers exhibit very low dielectric losses in the GHz region and it is difficult to heat them by microwaves [8].…”
Section: Introductionmentioning
confidence: 99%
“…The method yields a heating efficiency as high as 70% and a drastic increase in the amount of heat generated when the added CNT content reaches the percolation threshold [28]. However, in microwave-based curing processes, because an inhomogeneous electrical conductivity (such as in the presence of CNT aggregates) may induce localized heat generation (Figure 1b) [28][29][30][31], it is clear that the distribution of CNTs must be taken into account for an accurate evaluation of the residual stress. Whereas numerical simulations can be used to assess the effect of an inhomogeneous CNT distribution on residual stress, simulations of this kind have yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the expedition has taken researchers to the alternate rapid curing techniques using UV rays, Gamma rays, electron beam, and microwave irradiation . However, microwave offers advantageous effect on polymers curing because of its selective heating with faster and effective curing technique compared to other methods of curing and numerous researchers have devoted to investigating this technique for synthesis and manufacturing polymer nanocomposites . Microwave curing resulted in shorter curing time with higher strain to failure of the composites, improving the exfoliation of epoxy nanocomposite without compromising the mechanical properties of nanocomposites .…”
Section: Introductionmentioning
confidence: 99%
“…The bulk substrate was found to be unchanged, although high temperature was generated which may be because of short time of heat conduction during the attachment without damaging the chemical bonding of substrates. An interesting study on energy consumption during curing of epoxy based nanocomposites revealed that epoxy system with 0.5–1 wt % of CNT require 40–50% less energy than that required for net epoxy curing under microwave irradiation . Moreover, the energy consumption for conventional cured nanophased composites was found to be 3.5–5 times higher than the energy consumption during microwave curing with subtle change in mechanical properties of the nanocomposites .…”
Section: Introductionmentioning
confidence: 99%